Analyzing Muslim women’s leadership: the contemporary context - Ali, Md. Yousuf (Bangladesh Institute of Islamic Thought (BIIT), 2013)
Women’s leadership has become a contentious issue in the contemporary history of some Muslim societies. While it has been allowed by some Islamic scholars according to the necessity of the society in modern context, it has been largely rejected by majority Islamic scholars for its debilitating effects. Instances of women’s leadership in general and as heads of the Muslim states can be found in the context of the success of Benazir Bhutto in Pakistan, Khalida Zia and Sheikh Hasina in Bangladesh, Megawati Sukarnoputri in Indonesia, Atifete Jahjaga in Kosovo, Roza Otunbayeva in Kyrgyzstan, and Mame Madior Boye in Senegal. The contentious issue is debatable because no clear-cut direction was stated regarding the headship of the state and high government position that makes the issue divisive and conflict-ridden.